THE INFLUENCE OF CULTURAL STRUCTURE TOWARD GENDER STEREOTYPES IN THE FILM FROZEN 2 BY JENNIFER LEE - Rahmasari, Aulya; Panggabean, Waladdin (Faculty of Letters Universitas Balikpapan, 2025)
This study examines the influence of cultural structure on gender stereotypes in